An European perspective on regulating psychology: A review of the European Commission’s mutual evaluation of regulated professions - Karayianni, Eleni (Psichologija, 2018)
The article provides a summarized review of the current legal status of the profession of psychology across European countries, making a case for the need of a legal status and recognition of the profession. The review is based on comparing and contrasting the results of the European Commission’s mutual evaluation of the regulated professions report published in 2016 and the currently available information on the EU Single Market Regulated Professions Database maintained by the European Commission. Results show that, despite the different levels of qualifications required in the Member States, the general requirements tend to follow the Bologna process. The review also focuses on the rationale provided for regulation and the requirement for professional membership.